THE USE AND SYMBOLISM OF ANIMALS IN THE WONDERFUL WIZARD OF OZ - Taymaa Hussein Kheirbek; Roza Awat Ezzat (Universitas Islam Sumatera Utara (UISU), 2020)
This paper is the result of a qualitative research that follows an animal-based interpretative theory. It sheds the light on the use and symbolism of animal characters in The Wonderful Wizard of Oz written by L. Frank Baum and published in 1900. It seems to be a modern fairy tale with an American setting and charming fantasy characters. It is an immensely popular text among children and adults, so it is considered a classic of children's literature. It also attempts to answer why and how Baum used animals; whether for their qualities or for the sake of creating characters opposite to their symbolism. Therefore, the role and function of animal characters are extensively discussed. The findings show how L. Frank Baum presents a distinguished world from a non-human perspective and at the same time he teaches morality, religion, and accepting diversity in nature in an exciting narrative full of adventures. These animal characters can serve as a symbolic role models for young readers.